Biologi dan statistik demografi Thrips parvispinus Karny (Thysanoptera: Thripidae) pada tanaman cabai (Capsicum annuum Linnaeus) - Rudi Tomson Hutasoit; Hermanu Triwidodo; Ruly Anwar (Jurnal Entomologi Indonesia, 2017)
Thrips parvispinus Karny (Thysanoptera: Thripidae) is one of the major pests of chili pepper in Indonesia. The pest can be found on all parts of the plants, especially flowers and leaves. Information of the biology and demographic statistic of T. parvispinus are still limited. The objective of this research was to study the biology and demographic statistic of T. parvispinus in Bogor. Fifty individual of 1st instar nymphs were reared on caged chili pepper leaves (d = 4 cm and h = 8 cm). Chilli pepper leaves were replaced everyday and observed daily to determine the development and number of offspring eggs. The collected data were used to obtain information about the biology of the pest such as the stadia of each instar, preoviposition period, life cycle, adult longevity, and fecundity. The data were also used to construct life tables for demographic statistic analysis using of the Jackknife method. There were 5 phases of immature stages of T. parvispinus: eggs, two instars nymph, prepupa, and pupa with their stadia were 4,79, 1,36, 3,54, 1,08, and 1,96 days respectively. The preoviposition period of the insect was 1,11 days, life cycle was 13,68 days, female longevity was 8,55 days, male longevity was 6,00 days, and fecundity was 15,33 eggs per female. The population development of T. parvispinus followed type III of survivorship curve with intrinsic rate of increase was 0,15 individual per days female per days, net reproductive rate was 5,71 individual per female per generation, generation time was 11,49 days and doubling time was 4,57 days.